Hegel and modern society - Taylor, Charles 1931- (Cambridge philosophy classics, 2015)
This rich study explores the elements of Hegel's social and political thought that are most relevant to our society today. Combating the prevailing post-World War II stereotype of Hegel as a proto-fascist, Charles Taylor argues that Hegel aimed not to deny the rights of individuality but to synthesise them with the intrinsic good of community membership. Hegel's goal of a society of free individuals whose social activity is expressive of who they are seems an even more distant goal now, and Taylor's discussion has renewed relevance for our increasingly globalised and industrialised society. This classic work is presented in a fresh series livery for the twenty-first century with a specially commissioned new preface written by Frederick Neuhouser